Green Innovation as a Strategy for Empowering Batik MSMEs: Improving Productivity and Diversification toward Sustainable Green Industry in Pasuruan Regency - Antin Rakhmawati; Wisma Soedarmadji; Khoirul Huda; Muhammad Nizar; Lumhatus Shofi Sa'adah; Ridho Hafiz Maulana (LP2M INSURI Ponorogo, 2025)
The empowerment program for the Batik Canting Cantik community in Pasuruan Regency aims to strengthen the productivity, competitiveness, and sustainability of traditional hand-drawn Batik through the implementation of green innovation. Using a Participatory Action Research (PAR) approach, the study involved 15 artisans over six months through a series of participatory activities, including training, co-design workshops, production trials, and evaluation sessions. Artisans were trained in eco-printing techniques that utilize environmentally friendly natural dyes as alternatives to synthetic dyes, which are known contributors to hazardous waste. Technological innovations such as the introduction of steamers and multifunctional Batik dryers were also implemented to accelerate production processes and reduce dependency on weather conditions. The results show a 50% increase in productivity, a significant reduction in drying time, improved color durability, and enhanced product quality. In addition, marketing capacity was strengthened through training in branding, innovative packaging design, and digital marketing, including the use of social media and online marketplaces, which contributed to a broader national and international market reach. Beyond economic impacts, the program also generated environmental and social benefits by raising awareness of natural resource conservation and promoting sustainable cultural production practices. These findings demonstrate that green innovation is effective in enhancing the competitiveness and long-term sustainability of Batik-based MSMEs.